A Single Dose of Methylprednisolone Improves Aversive Memory Consolidation and Extinction in Rats - Gonçalves, Rithiele; Vargas, Liane da Silva de; Mello-Carpes, Pâmela B. (Frontiers in Neuroscience, 2019)
Aversive memory is essential for survival, but in some situations its exacerbation can be potentially dangerous. There are several ways to modulate memory, among them, through stress-related hormones physiological release or administration of exogenous substances analogous to them. Recently, our group shown that a chronic treatment with a low dose of methylprednisolone (MP) is able to promote memory persistence in rats. Herein, we evaluate if a single intraperitonial dose of MP (5 mg/kg) is able to modulate aversive memory consolidation and promote memory persistence and extinction in rats. For this, two experiments were carried out. In the first one, we demonstrated that a single IP MP administration in specific times after inhibitory avoidance training improved memory consolidation and persistence. In the second experiment, we verified that a single IP MP administration 2h after IA extinction training promoted memory extinction. This results suggest a possible new clinical applicability for MP on the aversive memory disorders, as post-traumatic stress.